Analisis SWOT Technology Financial (FinTech) Terhadap Industri Perbankan - Ratnawaty Marginingsih (Cakrawala - Jurnal Humaniora, 2019)
Abstract - The development of financial technology ( FinTech ) in Indonesia in recent times is very fast. Of this has been changing lifestyle community all sector of the local economy, one exception is in the financial which has the effect of to institutions financial service sectors contributed the country banking sector. The utilization of technology this provides a real challenge and the threat of an by himself and for of banking industry in the form of the strength and weakness that has been so there was a moment this to keep in can continue giving the best services. Using SWOT analysis can be material for making strategic planning and achieving goals short term both companies as well as long term in a more systematic by the banking industries. The research suggests the development of digital technology have impacted very large FinTech in the industry in the financing sector and this is unavoidable. Strengthening infrastructure that are becoming more adequate technology service providers are able to encourage financial collaborated and coordinated with other financial industry so that it can complement each other in meeting the people needs which in turn would increase national financial inclusion.Keywords: SWOT Analyses, Technology Financial, Banking IndustryAbstract  - Perkembangan Financial Technology (FinTech) di Indonesi dewasa ini sangat pesat. Hal ini telah mengubah gaya hidup masyarakat diberbagai sektor, salah satunya adalah di sektor finansial yang berdampak terhadap institusi jasa keuangan sektor perbankan. Pemanfaatan teknologi ini memberikan suatu tantangan dan ancaman tersendiri bagi industri perbankan  berupa kekuatan dan kelemaahan yang telah ada saat ini untuk tetap dapat terus memberikan pelayanan yang terbaik. Menggunakan analisa SWOT dapat menjadi bahan untuk membuat perencanaan strategis dan mencapai tujuan perusahaan baik jangka pendek maupun jangka panjang secara lebih sistematis oleh para pelaku industri perbankan. Hasil penelitian menujukkan perkembangan teknologi digital telah memberi dampak yang sangat besar terhadap pertumbuhan industri FinTech yang masuk ke sektor pembiayaan dan hal ini tidak dapat dihindari. Penguatan infrastruktur yang semakin memadai mampu mendorong penyedia jasa teknologi financial berkolaborasi dan bersinergi dengan industri keuangan lainnya, sehingga mampu saling mengisi dalam memenuhi kebutuhan masyarakat yang pada akhirnya dapat meningkatkan inklusi keuangan nasional.. Keywords: Analisis SWOT, Technology Financial, Industri Perbankan